The Influence of Environment, Lifestyle, Stress, and Activity on Mothers' Readiness to Face Menopause at the Kalumpang Community Health Center - Ismawati Sawedi (Manunggal Halim Jaya, 2026)
Menopause in women is the cessation of menstruation, which is a very complex period because it is related to physical and psychological conditions. The purpose of this study was to determine the direct and indirect influence of social environment, lifestyle, stress, and physical activity on maternal readiness to face menopause at the Kalumpang Ternate Community Health Center, North Maluku in 2017. This research method is a quantitative approach with a cross-sectional design. The research sample was 50 respondents. The analysis method used was the Structural Equation Model (SEM) with SmartPLS 2.0 and SPSS 20. The results of the hypothesis testing were that the variable of premenopausal maternal readiness in the Kalumpang Ternate Community Health Center Working Area, North Maluku was influenced by the environment (17.06%), lifestyle (23.39%), stress (19.21%) and physical activity (31.89%). The direct influence of premenopausal maternal readiness was 80.2% and the indirect influence was 5.72%. Physical activity is a dominant factor that greatly influences the readiness of premenopausal mothers, where the higher the physical activity of premenopausal mothers, the better the mother's readiness to face menopause, and conversely, the lower the physical activity, the worse the mother's readiness to face menopause. Research suggestions are expected for the community, especially families, to provide more support and attention to premenopausal mothers so that in facing menopause later there will be no anxiety that can disrupt the lives of mothers and families.